Thermal windows and metabolic performance curves in a developing Antarctic fish - Todgham, Anne; Miller, Nathan (IEDA: US Antarctic Program Data Center, 2017)
Abstract: This dataset includes data from the publication Flynn and Todgham 2017 - Thermal windows and metabolic performance curves in a developing Antarctic fish. Included are data on embryo survival, development, and metabolic rate.